STATE YOUTH POLICY AS THE BASIS OF SOCIO-ECONOMIC DEVELOPMENT (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, the author approached the topic of youth as a priority direction of state social policy, and the problem of youth is one of the most pressing today. The article analytically highlights that this socio-demographic layer of the population is the main criterion for the implementation of state policy.